Representasi Spiritualitas dan Romantisme dalam Lagu Munajat Cinta Analisis Semiotika Roland Barthes - Adib Fikri Ghozali (BAYAN: Jurnal Studi Islam dan Humaniora, 2025)
Music is a manifestation of human intellectuality and imagination combined with rhyme and tone as a means of conveying deep expression. This study analyzes the representation of spirituality and romance  in  the  song  Munajat  Cinta  by  Ahmad  Dhani  and  T.R.I.A.D.  using  Roland  Barthes' semiotic  approach.  This  qualitative  descriptive  study  explores  the  denotative  and  connotative meanings  in  the  song's  lyrics  to  understand  the  messages  contained  therein.  The  results  of  the analysis  show  that  this  song  represents  the  meaning  of  spirituality  through  an  individual's relationship  with  God,  such  as  prayer,  surrender,  and  spiritual  reflection.  The  lyrics  reveal  the meaning of tawakal and a sense of devotion to God as a source of strength. On the other hand, the dimension of romance is seen from the emotional expression of the struggle for love, trauma, and the desire for sincere love. Symbols such as "wilted roses" strengthen the narrative about the fragility of feelings and the search for happiness. Munajat Cinta is not only a musical work, but has a representation of the meaning of deep spirituality and romance.